2013
DOI: 10.4152/pea.201305277
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Protection of Hot Dip Galvanized Steel in Mortar

Abstract: Corrosion of steel in concrete is one of the major causes of structure degradation, requiring expensive maintenance. The using of hot dip galvanized steel (HDGS) has been recognized as one effective measure to increase the service life of reinforced concrete structures in marine environmental. However, HDGS corrodes in contact with high alkaline environment of fresh concrete. Although this initial corrosion process allows the formation of a protecting layer barrier, the corrosion that occurs initially is harmf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…The edges of both CE and WE plates, as well the non-active areas and connecting zones were protected with a dual-component epoxy resin (Araldite) using a previously established protocol. [27][28][29] For comparison purposes, cells prepared with non-coated HDGS WE electrodes were used as control. To assemble the electrochemical cells, 120 ± 10 g of fresh mortar was transferred to a 100 mL polyethylene flask, the electrodes were subsequently immersed and the flask closed.…”
Section: Macrocell Current Density (I Gal )-mentioning
confidence: 99%
See 1 more Smart Citation
“…The edges of both CE and WE plates, as well the non-active areas and connecting zones were protected with a dual-component epoxy resin (Araldite) using a previously established protocol. [27][28][29] For comparison purposes, cells prepared with non-coated HDGS WE electrodes were used as control. To assemble the electrochemical cells, 120 ± 10 g of fresh mortar was transferred to a 100 mL polyethylene flask, the electrodes were subsequently immersed and the flask closed.…”
Section: Macrocell Current Density (I Gal )-mentioning
confidence: 99%
“…27 A titanium-activated wire with a length of one cm was used as a reference electrode (RE) and a HDGS plate with an active area of 2 cm 2 coated with OIH was used as a working electrode (WE). The electrodes were connected to an isolated copper cable and the cutting zone of the tip of the titanium electrode was covered with dual-component epoxy resin (Araldite).…”
Section: Open Circuit Potential Monitoring (E Corr )-mentioning
confidence: 99%
“…The results also indicated that the i gal cells in SCPS were sensitive to the external laboratory temperature variation, to the presence of chloride ions and to the composition of the OIH material deposited which is also according to the literature. 44,46 Polarization resistance (R p ).- Figure 11 shows the R p values obtained for the different electrochemical cells prepared with HDGS coated by one dip step (1 layer), that were immersed in SCPS during 16 days. Results for control samples are also presented.…”
Section: Macrocell Current Density (I Gal )-mentioning
confidence: 99%
“…27,44 For comparison purposes, cells prepared with uncoated HDGS WE electrodes were used as control and triplicate cells were assembled to check data reproducibility. To assemble the electrochemical cells, the SCPS was transferred to a 100 mL polyethylene flask.…”
Section: Macrocell Current Density (I Gal )-mentioning
confidence: 99%
See 1 more Smart Citation